Proteomics in the COVID‐19 Battlefield: First Semester Check‐Up - Grenga, Lucia (Proteomics, 2020)
Proteomics offers a wide collection of methodologies to study biological systems at the finest granularity. Faced with COVID‐19, the most worrying pandemic in a century, proteomics researchers have made significant progress in understanding how the causative virus hijacks the host's cellular machinery and multiplies exponentially, how the disease can be diagnosed, and how it develops, as well as its severity predicted. Numerous cellular targets of potential interest for the development of new antiviral drugs have been documented. Here, the most striking results obtained in the proteomics field over this first semester of the pandemic are presented. The molecular machinery of SARS‐CoV‐2 is much more complex than initially believed, as many post‐translational modifications can occur, leading to a myriad of proteoforms and a broad heterogeneity of viral particles. The interplay of protein–protein interactions, protein abundances, and post‐translational modifications has yet to be fully documented to provide a full picture of this intriguing but lethal biological threat. Proteomics has the potential to provide rapid detection of the SARS‐CoV‐2 virus by mass spectrometry proteotyping, and to further increase the knowledge of severe respiratory syndrome COVID‐19 and its long‐term health consequences.